The Use of Rapeseed Husks to Remove Acidic and Basic Dyes from Aquatic Solutions - Tomasz Jóźwiak; Urszula Filipkowska (Applied Sciences, 2024)
This study aimed to identify the possibility of using rapeseed husks (RH) as an unconventional sorbent for removing acidic (AR18, AY23) and basic (BR46, BV10) dyes from aqueous solutions. Its scope included, i.a.: sorbent characterization (FTIR, pHPZC), determination of pH effect on dye sorption effectiveness (pH 2–11), analysis of dye sorption kinetics (pseudo-first order model, pseudo-second order model, intraparticular diffusion model), and the determination of the maximum sorption capacity (Langmuir 1 and 2, and Freundlich isotherms). The sorption effectiveness of acidic dyes (AR18, AY23) onto RH was the highest at pH = 2, whereas that of the basic dyes BR46 and BV10 was most effective at pH = 6 and pH = 3, respectively. The time needed to reach the sorption equilibrium of dyes onto RH depended on their initial concentration and ranged from 120 to 150 min for the acidic dyes and from 150 to 180 min for the basic dyes. The maximum sorption capacity (Qmax) of RH towards AR18 and AY23 was 49.37 mg/g and 41.52 mg/g, respectively, and towards BR46 and BV10 it was 59.07 mg/g and 20.93 mg/g, respectively. The obtained Qmax values were compared with the results achieved for other sorbents (literature data). This comparison demonstrated that the sorption capacity of rapeseed husks towards the analyzed dyes was higher compared to that of some types of activated carbons.